ADAPTATION AND VALIDATION OF THE TURKISH VERSION OF THE BATH ANKYLOSING SPONDYLITIS DISEASE ACTIVITY INDEX (BASDAI) - Saime Ay; Şehim Kutlay; Yeşim Kurtaiş; Burcu Yanık (Archives of Rheumatology, 2004)
The aim of this study was to adapt the Bath Ankylosing Spondylitis Disease Index (BASDAI) questionnaire for use in Turkey and to test its reliability and validity. Following standart adaptation procedure of BASDAI, we performed the Turkish version. A total of 76 patients with ankylosing spondylitis were assessed with the BASDAI, the Turkish version of the Bath Ankylosing Spondylitis Functional İndex (BASFI), the Bath Ankylosing Spondylitis Metrology İndex (BASMI), the Bath Ankylosing Spondylitis Patient Global Score (BAS-G). Reliability of the adapted version was good, with high internal consistency (cronbach’s alpha 0.76) and test-retest reliability (spearman’s Rho 0.88) as was the distribution of scores across the scale (score range:0.1-8.9; md:3.3). The correlation coefficient between the BASDAI and the BASFI was rs=0.61, between the BASDAI and the BASMI rs=0.21 and between the BASDAI and the BAS-G rs=0.46. Conclusions: Adaptation of the BASDAI for use in Turkey is succesful. The results of the present study indicate that the Turkish version of BASDAI is reliable and valid. It is a comprehensive self-administered instrument for assessing disease activity.